Deleuze and religion - Bryden, Mary, 1953- (Routledge, 2001)
This collection of essays explores the religious implications and connections of Deleuze's thinking. It sets his writing in the context of a wide spectrum of textual material, including patristics, mysticism, dogmatic theology and literature.